Congenital onychodysplasia of the index finger in a newborn. - Arias Linthon, Stephany; Giraldo Parra, Maria Jose; Valderrama Ávila, Alix Jessika (European Journal of Pediatric Dermatology, 2025)
Congenital onychodysplasia of the index finger (COIF), also known as Iso-Kikuchi syndrome, is a rare and often underdiagnosed condition. While most cases are sporadic, a hereditary component has also been described. Its pathophysiology remains unclear but is associated with maternal medication use during pregnancy, alterations in the Wnt signaling pathway, and intrauterine ischemic events. Clinically, it is characterized by micronychia, polyonychia, anonychia, and irregular lunulae, predominantly affecting the index fingers and, less commonly, the toes. Currently, there are no standardized treatment options.